2011
DOI: 10.1186/1465-9921-12-85
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of the airway wall in asthma: fibered confocal fluorescence microscopy in relation to histology and lung function

Abstract: BackgroundAirway remodelling is a feature of asthma including fragmentation of elastic fibres observed in the superficial elastin network of the airway wall. Fibered confocal fluorescence microscopy (FCFM) is a new and non-invasive imaging technique performed during bronchoscopy that may visualize elastic fibres, as shown by in vitro spectral analysis of elastin powder. We hypothesized that FCFM images capture in vivo elastic fibre patterns within the airway wall and that such patterns correspond with airway h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 31 publications
2
19
0
3
Order By: Relevance
“…These data are in agreement with another study that demonstrated significant associations between elastic fiber assembly patterns and postbronchodilator FEV 1 % predicted (31). Our data suggest that increased elastin gene expression is associated with increased post-bronchodilator FEV 1 /FVC, or less airway obstruction, and that elastic fiber staining in airway biopsy tissue is directly correlated with methacholine PC 20 , or inversely correlated with AHR in asthma.…”
Section: Discussionsupporting
confidence: 82%
“…These data are in agreement with another study that demonstrated significant associations between elastic fiber assembly patterns and postbronchodilator FEV 1 % predicted (31). Our data suggest that increased elastin gene expression is associated with increased post-bronchodilator FEV 1 /FVC, or less airway obstruction, and that elastic fiber staining in airway biopsy tissue is directly correlated with methacholine PC 20 , or inversely correlated with AHR in asthma.…”
Section: Discussionsupporting
confidence: 82%
“…The distribution of elastic fibres in the bronchial wall was classified as lamellar, loose and mixed pattern according to its orientation, as previously described,11 and it was later confirmed by pathological examination. Fluorescence intensity was quantified using the MedViewer Signal Quantification Toolbox as previously described,6 7 and the ratio between the alveolar/bronchial wall fluorescence intensity (ABI) was calculated 6…”
Section: Methodsmentioning
confidence: 74%
“…As shown in figure 1, using FCFM we recognised the three previously described11 patterns of bronchial wall fibre distribution (lamellar, loose and mixed patterns). The lamellar pattern was characterised by a linear and parallel bronchial thick fibre orientation (figure 1A), in the loose pattern the fibres were thin and non-specifically orientated (figure 1C) and the mixed pattern showed a combination of the two (figure 1E).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…At finer resolutions, optical techniques such as intravital (59) and confocal microscopy (27, 103,118,137) provide cellular-level imaging, aided by the use of intrinsic or exogenous fluorophores (59). However, such optical techniques provide insight only over very superficial surface layers and small fields of view.…”
mentioning
confidence: 99%